Unveiling the Underlying Factors and Ripple Effects of Electoral Violence in the Tamale Metropolis - Mohammed, Siibaway; Majialuwe, Eric Kojo; Titigah, Gregory (Advances in Social Sciences Research Journal, 2024)
This study reveals the underlying factors promoting electoral-related violence and its effects in the Tamale metropolis. The case study design guided the research, with a mixed-methods approach used for the data collection. Two hundred and fifty closed and open-ended questionnaires were administered to respondents, while five key informant in-depth interviews were conducted. Quantitative data was analysed using the Statistical Package for the Social Sciences (SPSS), and a thematic approach was used to analyse the qualitative data obtained from the study. It was revealed that electoral violence is engendered by multifaceted root causes, encompassing political, social, and economic dimensions. However, poverty was noted as the leading cause of electoral violence in the Tamale metropolis, representing 34.8%. The research found that election-related violence has significant effects on the socio-economic development of Tamale metropolis. These include the maiming of people, deaths, and destruction of public and private properties. These findings confirm the conceptual framework on which this study is anchored. Drawn from identity and interest-group theories, the conceptual framework posited that election-related violence leads to loss of lives, loss of property, harassment of citizens, displacement of citizens, disruption of public order, and maiming of citizens. It was further established that addressing the problem of electoral violence in the Tamale metropolis requires a comprehensive and multi-faceted approach that involves various stakeholders, including government agencies, civil society organisations, political parties, and the local community. Therefore, it is recommended that the government work in collaboration with non-governmental and civil society organisations and community stakeholders to address poverty among youth by creating employment opportunities. This has the potential and significant tendency to reduce the influence of politicians in inciting the youth to indulge in electoral violence-related activities.